Characteristics of corn starch/chitosan blend green polymer electrolytes complexed with ammonium iodide and its application in energy devices / Yuhanees Mohamed Yusof - Yuhanees, Mohamed Yusof (2017)
In the present work, a polymer electrolyte (PE) system comprises of corn starch/chitosan blend biopolymer electrolyte as host and ammonium iodide (NH4I) as proton provider is prepared by solution casting technique. Fourier transform infrared spectroscopy (FTIR) analysis has proved the interactions between the components. The highest room temperature conductivity of (3.04 ± 0.32) × 10-4 S cm-1 is obtained when the polymer host is doped with 40 wt.% NH4I. The conductivity is further enhanced to (1.28 ± 0.07) × 10-3 S cm-1 with the addition of 30 wt.% glycerol. Transport study has proved that the conductivity is influenced by the number density (n) and mobility of ions (). The conductivity-temperature analysis of all electrolytes is found to follow the Arrhenius rule. Dielectric studies confirm that the electrolytes obey non-Debye behavior. The ionic transference number measurement confirms that ion is the dominant conducting species. The cation transference number (t+) for the highest conducting electrolyte (B3) is found to be 0.40. Thermogravimetric analysis (TGA) reveals that the plasticized electrolyte is stable up to 150°C. The characterization techniques including X-Ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and differential scanning calorimetry (DSC) have verified the conductivity trend. Linear sweep voltammetry (LSV) is carried out prior to fabrication in electrochemical devices. B3 electrolyte is electrochemically stable up to 1.90 V and suitable to be applied in batteries and EDLCs. Cyclic voltammetry (CV) and galvanostatic charge-discharge measurements are carried out for EDLC characterization. The primary proton batteries are discharged at different constant currents while the secondary proton battery has been charged and discharged at 0.40 mA for 60 cycles.